Current Legal Problems in Interpreting International Civil Aviation Law (Frontiers in Law, 2023)
The progress of international civil aviation law is anchored on two main sources: The Convention on International Civil Aviation (Chicago Convention); and Resolutions adopted by the Assembly of the International Civil Aviation Organization (ICAO). These two sources give rise to subsidiary guidance in the form of Annexes to the Convention and manuals on various subjects that address international civil aviation. However, there is no cohesive link between the two sources as well as there being no formal recognition by ICAO of the legal status of Assembly Resolutions, although such resolutions are adopted at each ICAO Assembly with monotonous regularity. Added to this conundrum is the lack of clarity in the interpretation of the Convention itself, which empowers the Council of ICAO to adopt Annexes to the Convention (which, according to the Convention are so named for convenience) while at the same time taking away any legal obligation of the member States to adhere to the Standards contained in the Annexes. This article discusses the nature of international civil aviation law against the backdrop of treaty law and examines the legal issues that arise from the interpretation of the Chicago Convention and Resolutions adopted by the ICAO Assembly.